High prevalence of G12P[8] rotavirus strains in Rio Branco, Acre, Western Amazon, in the post‐rotavirus vaccine introduction period. Issue 5 (3rd November 2015) - Neves, Mayara A.O.; Pinheiro, Helder H.C.; Silva, Rita S.U.; Linhares, Alexandre C.; Silva, Luciana D.; Gabbay, Yvone B.; Silva, Mônica C.M.; Loureiro, Edvaldo C.B.; Soares, Luana S.; Mascarenhas, Joana D'Arc P.
Abstract : The present study aimed to provide a molecular characterization of circulating rotavirus (RVA) strains in Rio Branco, Acre, in the post‐rotavirus vaccination period, particularly with regard to the emerging, increasingly prevalent G12P[8] genotype. A total of 488 fecal specimens from diarrheic and non‐diarrheic children were obtained between January and December 2012. RVA detection was initially performed using enzyme‐linked immunosorbent assay (ELISA) method, followed by reverse‐transcription polymerase chain reaction (RT‐PCR) using specific primers. RVA was detected in 18.3% (44/241) of the children with acute diarrhea and in 1.2% (3/247) of the non‐diarrheic children ( P < 0.001), with overall RVA‐positivity of 9.6% (47/488). The most common genotype was G2P[4] with 43.2% (19/44) of the diarrheic cases, followed by G12P[8] (27.3%, 12/44), G3P[6] (18.2%, 8/44), G3P[8] (4.5%, 2/44), and G12P[6] (2.3%, 1/44). G12 samples belonged to lineage III and were from children aged 4–52 months. All of these children had acute diarrhea associated with fever (83.3%, 10/12) and vomiting (66.7%, 8/12). Most of the cases occurred in August (58.3%, 7/12), 75% (9/12) of which having received the full vaccination scheme with Rotarix™. For the first time G12 was reported at relative high prevalence in Brazil. Our findings warrant further monitoring studies on the molecular characterization of circulating RVA strains after rotavirus vaccine introduction in Brazil and elsewhere, since the occurrence of either unusual our emerging genotypes may pose a challenge to vaccination strategies. J. Med. Virol. 88:782–789, 2016 . © 2015 Wiley Periodicals, Inc.